Media Pembelajaran Interaktif Berbasis Articulate Storyline Dalam Pembelajaran Bahasa Arab - 'Azza, Faridatul; Indah Fatimatul Djamilah, Wulan (Tarling : Journal of Language Education, 2024)
As digital technology continues to advance, Arabic has an essential role in education in schools, especially in Indonesian Islamic school, this is because Arabic has an important role in understanding Islamic teachings. Although many students consider Arabic as a difficult language, the use of technology, especially Articulate Storyline, can increase interest and effectiveness of learning. Articulate Storyline is software that designed to allow teachers to make interactive and interesting learning materials. In this context, interactive learning media not only makes the learning process more enjoyable, but also helps students understand Arabic concepts better. The article research methodology is the literature methode. The study findings that Articulate Storyline is effective in improving Arabic language skills. Arabic language skills can be improved with the support of an articulate storyline. Students may get more involved in the learning process if this interactive medium is used. Despite these benefits, there are a number of drawbacks to using articulate storytelling. First, the creation process takes time and process. Second, this media cannot be accessed via IOS smartphones. Third, the screen display cannot be full when displayed on a smartphone, and audio is only heard on slides that are inserted with audio.